PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN ( Studi Pada Kantor Perum Perumnas Regional 5 Semarang ) - Piliang, Fadel Muhammad Reza; Rahardja, Edy (Diponegoro Journal of Management, 2015)
Employee's performance can be measured through job satisfaction and organizational commitment.The Purpose of the research is to describe how the variables influence job satisfaction and organizational  commitmen  to  employee  performance  of  office  Perum  Perumnas  Regional  5Semarang  and  to  determine  which  variables  are  the  dominant  influences  between  the  two variables.The population is every employee of office Perum Perumnas Regional 5 Semarang as much a65 employees. If the population is less than or close to a 100, then the population can be used as samples so that makes this a population research Arikunto (2006:134). Sampling technique of thisresearch is census, which is a technique of determining the sample when all the population is usedas samples. Data-testing technique used in the research include instrument testing (validity test, reliability test), classic assumption test (normality test, multicollinearity, heteroscedasticity test) multiple regression analysis, F-test, t-test, and coefficient of determination test (R2) by using SPSS16 application.The  result  shows  that  the  work  satisfaction  and  organizasional  commitment  influence positively and significantly to the employee performace. Value of determination coefisien or R square is 0,892, which means staff performance is affected by staff satisfication and organizational commitment as 89,2%.